The Role of Job Characteristics and Professional Commitment to Tenure and Performance (Study of Teachers in Public High Schools in Solo Raya) - Anggoro Panji Nugroho; Aris Tri Haryanto (Common Publisher, 2019)
The purpose of this study is to know and empirically test the role of job characteristics and professional commitment to work tenure and performance in high school teachers in Solo Raya. The unit of analysis is the individual because the answers of each respondent represent themselves, which in this study are teachers in Solo Raya covering Surakarta City, Boyolali District, Sukoharjo, Wonogiri, Sragen, Karanganyar, and Klaten. The sample used was 100 respondents. The analysis technique uses multiple linear regression analysis. The results showed that the characteristics of work had a positive and significant effect on the length of service. Professional commitment has a positive and significant effect on tenure. Job characteristics have a positive and significant effect on performance. Professional commitment has a positive and significant effect on performance. The length of service has a positive and significant effect on performance. The path analysis results show that the direct influence of job characteristics is an effective path to improve performance.